Rurubelle / Nur Azmina Syakirah Mohd Nizam and Nur Hazmida Husna Nor Azmy - Mohd Nizam, Nur Azmina Syakirah; Nor Azmy, Nur Hazmida Husna (2022)
Rurubelle main focus of the business is beauty and skincare products. Rurubelle is an agent under a famous local skincare brand, Ruruberry which offer various skincare products such as facial wash and serum. Rurubelle motto is “Taking care of your skin is more important than covering it up.” It delivers to people that a beautiful glowing make up look comes from a healthy skin. Rurubelle is an online business that started solely on Facebook by both Nur Hazmida Husna and Nur Azmina Syakirah. It was established in November of 2021. Name of Business The name of this online business is agreed to be as Rurubelle which stands for Ruruberry which is the brand original name and combine it with the word belle. However, the business address our business is located at 204, Jalan 4 D’Latania, Taman Bandar Senawang, 70450 Seremban, Negeri Sembilan and 321, Jalan Pinggiran Tanjung 2B, Desa Pinggiran Bayu, 71700 Mantin, Negeri Sembilan, since we are doing an online business so we juat do it at our home. Form of business and main activities of this business is a partnership between Nur Hazmida Husna and Nur Azmina Syakirah where we both coming up with the idea of the business. Bank Account We opened a new bank account to separate the business fund and personal fund. Also, we creating a new email for this business which is rurubelle.byhm@gmail.com as our official business email. Therefore, we have our mission for Rurubelle and it is to be one of the most preferred skincare company by providing a safe and effective product for a flawless skin. While our vision is to provide everyone with a clean, self-sufficient option that promotes self-care and enrich the skin, to make sure that people will change the mindset that local product is not safe for the skin and to spread awareness of choosing the product that is vegan and cruelty-free. There are many products of Ruruberry that we sell on our Facebook (Fb) Page and we are including all the teaser, hard sell, and soft sell.